TEACHING THE ACCOUNTANT THE HISTORY AND ETHICS OF HIS PROFESSION. - Myer, Joseph C. (The Accounting Review, 1931)
Abstract Many accountants have lack of knowledge of their own profession. Neither they have the desire to gain knowledge. Not only the historical aspects of accountancy are unknown but important matters as laws affecting the profession, societies of accountants, and the ethics absolutely essential to the proper practice of accountancy are unheard of in some cases. The study of history of one's profession, acquaints a student with the mistakes and the achievements of those who preceded him. The study of fact and conditions is important as it gives the student reasoning ability that later will permit him to apply such remedies and measures that are necessary to turn possible failures into successes. Specifically, the accountant who merely has his knowledge of debit and credit, or who knows a chart of accounts and has had training in recording facts in books of account will not succeed unless he knows how to present these facts to his client in such manner as to preclude any misunderstanding.